Automatic Stacking Crane Prototype using Microcontroller Arduino Mega 2560 - Sardono Sarwito; Indra Ranu; Fajar Andik Cahyono (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2016)
The port is one of the supporting infrastructures for sea-transportation carrying goods and passengers. The function of port is important in supporting the transportation system to develop economic, social, and eduaction with sea-trading as booster. Crane is device which use to lift or move heavy loads and commonly was used in ports for container loading - unloading process. This research will create automatic stacking crane prototype with an Arduino Mega 2560 as controller. There is a lack of this design is the incoming voltage to the motor sourced from this microcontroller module is 5 V. In hence, the spindle motor is not optimal. In addition, there are still many input response procedure was not appropriate.